Antimicrobial resistance in Neisseria gonorrhoeae isolates and gonorrhoea treatment in the Republic of Belarus, Eastern Europe, 2009–2019 - Aliaksandra Aniskevich; Iryna Shimanskaya; Iryna Boiko; Tatyana Golubovskaya; Daniel Golparian; Iryna Stanislavova; Susanne Jacobsson; Aliaksandr Adaskevich; Magnus Unemo (BMC Infectious Diseases, 2021)
Abstract Background Limited antimicrobial resistance (AMR) data for Neisseria gonorrhoeae are available in Eastern Europe. We investigated AMR in N. gonorrhoeae isolates in the Republic of Belarus from 2009 to 2019, antimicrobial treatment recommended nationally, and treatment given to patients with gonorrhoea. Methods N. gonorrhoeae isolates (n = 522) cultured in three regions of Belarus in 2009–2019 were examined. Determination of minimum inhibitory concentrations (MICs) of eight antimicrobials was performed using Etest. Resistance breakpoints from the European Committee on Antimicrobial Susceptibility Testing were applied where available. A Nitrocefin test identified β-lactamase production. Gonorrhoea treatment for 1652 patients was also analysed. Statistical significance was determined by the Z-test, Fisher’s exact test, or Mann-Whitney U test with p-values of < 0.05 indicating significance. Results In total, 27.8% of the N. gonorrhoeae isolates were resistant to tetracycline, 24.7% to ciprofloxacin, 7.0% to benzylpenicillin, 2.7% to cefixime, and 0.8% to azithromycin. No isolates were resistant to ceftriaxone, spectinomycin, or gentamicin. However, 14 (2.7%) isolates had a ceftriaxone MIC of 0.125 mg/L, exactly at the resistance breakpoint (MIC > 0.125 mg/L). Only one (0.2%) isolate, from 2013, produced β-lactamase. From 2009 to 2019, the levels of resistance to ciprofloxacin and tetracycline were relatively high and stable. Resistance to cefixime was not identified before 2013 but peaked at 22.2% in 2017. Only sporadic isolates with resistance to azithromycin were found in 2009 (n = 1), 2012 (n = 1), and 2018–2019 (n = 2). Overall, 862 (52.2%) patients received first-line treatment according to national guidelines (ceftriaxone 1 g). However, 154 (9.3%) patients received a nationally recommended alternative treatment (cefixime 400 mg or ofloxacin 400 mg), and 636 (38.5%) were given non-recommended treatment. Conclusions The gonococcal resistance to ciprofloxacin and tetracycline was high, however, the resistance to azithromycin was low and no resistance to ceftriaxone was identified. Ceftriaxone 1 g can continuously be recommended as empiric first-line gonorrhoea therapy in Belarus. Fluoroquinolones should not be prescribed for treatment if susceptibility has not been confirmed by testing. Timely updating and high compliance with national evidence-based gonorrhoea treatment guidelines based on quality-assured AMR data are imperative. The need for continued, improved and enhanced surveillance of gonococcal AMR in Belarus is evident.